Building the Administrative Capacity of District Assemblies in Ghana; Examining the Role of Staff Postings - Seim, P. (University of Ghana, 2015)
The study examined the role of staff postings as a tool for strengthening the administrative capacity of the District Assemblies in Ghana. The theory adopted for the interpretation of the findings was the theory of institutional integrity where the effectiveness of an institution is measured by its level of integrity or corruption. The methodological approaches used for the study were both qualitative and quantitative. Hence in-depth interviews and survey questionnaires were administered to solicit information from officials within the Local Government Service. The study found out that the establishment of the Local Government Service has helped to improve the administrative capacity of the District Assemblies in Ghana. Also, contrary to the widespread notion and various allegations that politics play a key role in the posting of Local Government Officials and that Officers do not accept postings to less resourced areas, it is largely not so in practice. The study found out that politics does not play any significant role in postings at the grassroots level but perhaps it is felt at the top management level and has not eaten deep to the lower management level. Furthermore, most Officials in the Local Government Service asserted that they will accept postings to less resourced areas. The study concluded by affirming that there is a high level of institutional integrity in terms of staff posting and the level of institutional corruption is very minimal. Therefore, the level of confidence that the employees have in the system is quite high. However, lack of a comprehensive database of employees and non-payment of the benefits that comes with staff posting is still a challenge in the Local Government Service.
Thesis (MPhil) - University of Ghana, 2015
Keywords: BUILDING; ADMINISTRATIVE; DISTRICT ASSEMBLIES; THE ROLE OF STAFF POSTINGS; EXAMINING